Burning Mouth Syndrome, Relationships with Some Systemic Medications (A clinical study among an Iraqi sample) - Mehdi A. Al-Rubayee; Sabah M. Damad; Ameena J. Lafta (College of Pharmacy / Mustansiriyah University, 2014)
Despite the numbers of studies upon burning symptoms in patients with clinically healthy appearance of the oral mucosa, as well as burning mouth syndrome (BMS) itself, they both remain still challenging subjects. The aim of this study was arranged to evaluate the effects of some systemic medication in the occurrence of BMS in relation to other etiological factors that may share in causing this disease in an Iraqi sample. Out of eighty, fifty patients (28 female and 22 males) were selected as a study group, all of them suffered from BMS, clinical and laboratory examinations in addition to previous diagnosis for the patients on the referral forma were depending on identifying the etiological causes for the BMS. This study revealed that antihypertensive and antidepressant medications were more affecting among this studied Iraqi sample with BMS than other etiological factor.